Analysis of Downtime Common Rail Deutz Technology Engine Using RCM Methods - Rachmat Darmawan; Fajar Azhari Julian; Novianti Rachmayani; Andri Mulyana; Abdul Rochim (Institut Teknologi Dirgantara Adisutjipto, 2026)
This study aims to analyze and minimize engine downtime on Deutz common rail technology using the Reliability Centered Maintenance (RCM) approach on the TMX-450 Pushback unit which is commonly used in the aviation industry. The analysis uses quantitative data based on downtime data and intervals related to downtime frequency data on injector components which have recorded failure parts with a frequency of 10 times and accumulated downtime of 21 hours. The results of the analysis on downtime values before and after the implementation of RCM are the inspection schedule increased from 5% to 12%, the repair schedule increased from 24% to 49%, the discharge schedule increased from 10% to 19%, and of course no treatment decreased significantly from 61% to 20%. The conclusion is that the implementation of RCM reduces total downtime by 30% and provides an increase in component reliability to 98.8% which shows that RCM is effective in optimizing maintenance scheduling.